SPICE simulation of memristive circuits based on memdiodes with sigmoidal threshold functions - Patterson, Germán Agustín (2018)
In this paper, a SPICE implementation of a memristive model is presented and put under test by means of different circuit configurations. The model is based on sigmoidal threshold functions that switch the parameters involved in the transport equation. Results show that the model is stable under different driving signals, in particular, in multielement circuits. Antiparallel and anti‐series configurations are investigated as well as its application to thresholding devices and 1R1S structures.